PERLINDUNGAN ISLAM TERHADAP BURUH - bin Lahuri, Setiawan (MUQTASID, 2013)
In Islam, the determination of wages is not only based on the quality of labor as the physical, mental, work experience, professionalism and so on. But there are other considerations, they are aspects of personal and family needs. Thus, there are important implications of the theory above, the Islamic theory of wage determination is in contrast to the capitalist economic system, and there are elements in common with the socialist economic system. Mechanisms of wage determination in Islam does not depend on the institutional market. Islam is a religion that upholds universal human valuesââ. Islam is very concerned with the rights and obligations of all people, including the workers and laborers. Teaching that can be seen from several hadith clearly provides real assurance that the workers have to work in a comfortable state, far from the threat of layoffs, delays in awarding salary, job demands beyond the limits of human ability and so on. Thus, Islam gives an overview of the importance of laborers and workers in human life. Islam gives us the importance of laborers and workers in human life. Islam thus providing strong values ââas a form of protection to the workers and employees.